Pengaruh prenatal yoga terhadap lama kala II persalinan dan kejadian robekan perinium - Noviani, Ni Wayan; Adnyani, Ni Wayan Sukma (Universitas Muhammadiyah Semarang, 2020)
Labor is assumed to be a painful and tense process, but labor can be passed with a sense of security and comfort without trauma. Yoga is considered one of the alternative therapies to prepare pregnant women physically, mentally, and spiritually to face the birth process and prevent perineal rupture. This study aims to determine prenatal yoga's effect on the duration of the second stage of labor and the incidence of perineal tears at the Bumi Sehat Foundation Ubud Bali in 2018. The study was conducted by analytic design with a prospective study approach. The research subjects used 50 pregnant women who gave birth at the Bumi Sehat Foundation. The study used Mann-Whitney and chi-square. Based on the data analysis of the influence between Prenatal yoga on the duration of the second stage of analysis using Mann-Whitney p-value <0.005 which means that there is an influence between prenatal yoga on the second time while based on Chi-square data analysis p-value 0.012 where p-value <0, 005 which means that there is an influence between Prenatal yoga and perineum tear. It can be concluded that prenatal yoga is effective in helping pregnancy and childbirth are minimally traumatic in women.